2006
DOI: 10.1093/rheumatology/kel019
|View full text |Cite
|
Sign up to set email alerts
|

Association of a non-synonymous single-nucleotide polymorphism of DNASEI with SLE susceptibility

Abstract: The association of the Gln244Arg SNP with SLE susceptibility indicates that common polymorphisms in DNASEI play a role in the genetics of SLE. However, the lack of effect of the Gln244Arg SNP on serum DNase I activity calls into question the direct involvement of this specific SNP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 30 publications
0
33
0
1
Order By: Relevance
“…144 Two SLE genetic studies related to DNase I performed in a Spanish population found that þ 2035C/G, which is in strong linkage disequilibrium with þ 2373A/G, was significantly associated with SLE. 145,146 Studies of DNase II, III and IV in Korean populations have found that none of these DNase subtypes were associated with SLE susceptibility. [147][148][149] However, genetic variants of DNase II (rs4804209, rs11085823 and rs2293682) were weakly associated with lupus nephritis, 147 and DNase III (Trex-1 and Trex-2) and IV showed associations with the development of SLEassociated autoantibodies.…”
mentioning
confidence: 99%
“…144 Two SLE genetic studies related to DNase I performed in a Spanish population found that þ 2035C/G, which is in strong linkage disequilibrium with þ 2373A/G, was significantly associated with SLE. 145,146 Studies of DNase II, III and IV in Korean populations have found that none of these DNase subtypes were associated with SLE susceptibility. [147][148][149] However, genetic variants of DNase II (rs4804209, rs11085823 and rs2293682) were weakly associated with lupus nephritis, 147 and DNase III (Trex-1 and Trex-2) and IV showed associations with the development of SLEassociated autoantibodies.…”
mentioning
confidence: 99%
“…19 Furthermore, recent studies have demonstrated that DNASE1 Ã 2 is more common in systemic lupus erythematosus patients than in control groups in Korean and Spanish populations. 20,21 Further evaluations of the relevance of DNase I to these diseases are required.…”
Section: Resultsmentioning
confidence: 99%
“…The atempt to connect low DNase I activity with high serum actin concentrations was then rejected [114]. Numerous eforts to identify genetic changes, which can inluence on the enzyme activity, resulted in very rare incidence of functionally signiicant gene alterations, about two per 1000 sequenced SLE patients [115][116][117]. Other important information, provided by geneticists, was markedly increased expression of DNase I gene in SLE [115].…”
Section: Lupusmentioning
confidence: 99%